Amelioration of ethanol-induced gastric ulcer in rats by quercetin: implication of Nrf2/HO1 and HMGB1/TLR4/NF-κB pathways - Shams Gamal Eldin Shams; Rana G. Eissa (Heliyon, 2022)
Gastric ulcer is a serious medical condition that can be developed due to an imbalance in the protective and destructive factors of the gastric system. Available therapies do not provide definite cure, thus, there is an urge to seek for alternative treatments. Quercetin is a natural flavonoid that possesses antioxidant and anti-inflammatory properties. In the current study, the antiulcerogenic effect of quercetin in ethanol-induced gastric ulcer (EI-GU) rat model was compared to Antodine® (a reference drug), to elucidate the potential underlying mechanisms. Quercetin (50 mg/kg) and Antodine® (20 mg/kg) were given orally for one week post ulcer induction by ethanol. EI-GU was associated with downregulation of SOD, CAT, Nrf2 and HO1, and accompanied by upregulation of inflammatory markers (i.e., HMGB1, NF-κB and TNFα) and an increase in Bax/Bcl2 ratio. Administration of quercetin resulted in a significant reduction in gastric volume in the stomach of ulcerative rats by 86% and a significant decrease in gastric lesion count by 3.5- folds, as compared with the ulcerative rats. Moreover, rats treated with quercetin showed upregulation of Nrf2 by 3.3-fold change and in HO1 by 3.5-fold change when compared to ulcerated rats, and decreased HMGB1, TLR4, NF-κB p65 and TNF-α by 50%, 53%, 52.9% and 54.9%, respectively. Treatment of rats with quercetin reduced Bax and Bax/Bcl2 ratio and increased Bcl2 relative to ulcerated rats. Thus, it can be concluded that the ulcerogenic curative properties of quercetin were mediated by antioxidant, anti-inflammatory and antiapoptotic activities.